HERMENEUTICS AND ITS IMPLICATIONS FOR UNDERSTANDINGTHE PRELIMINARY HADITS - Hidayatullah Ismail; Dasman Yahya Ma’ali; Mochammad Novendri S; Helmi Basri (Salwatuna : Jurnal Pengabdian Masyarakat, 2022)
: This article is entitled the hermeneutic method and its implications for understanding hadith. In understanding the hadith, there are hadiths that are not the same as the Koran, both at the level of certainty of the presence of the text (qaṭ'ī al-wurūdah) and at the level of certainty of the argument (qaṭ'ī al-dalālah). This article examines how the presentation of hermeneutics and its implications for the understanding of hadith. Using a descriptive-analytical approach, this study examines the basic concept of an interpretive approach to understanding a hadith. From the results of the discussion, it can be concluded that the hadith sciences that have been relied on so far, will be more evident in their effectiveness when complemented by a hermeneutic approach that examines not only the horizon of the text, but also the horizons of the initiator (Prophet), readers (rijal al-hadis, mukharrij al-hadith) and mufassir), and its contextuality. The hermeneutic approach in the interpretation of hadith can be carried out through three layers of interpretation, namely: (2) interpretation from "inside" the hadith text (meaning within the text); (2) interpretation of the things surrounding the hadith text (meaning behind the text); and, (3) critical interpretation of hadith texts (meaning in front of the text). These three layers of interpretation have focuses, goals, and methods that complement one another. Interpretation of hadith with a hermeneutic approach is felt to be able to generate meanings that combine the elements of textuality and contextuality of hadith at once, bearing in mind that a text can only find its meaning in context.